2018
DOI: 10.12688/f1000research.8729.3
|View full text |Cite
|
Sign up to set email alerts
|

Hypnotic drug risks of mortality, infection, depression, and cancer: but lack of benefit

Abstract: This is a review of hypnotic drug risks and benefits. Almost every month, new information appears about the risks of hypnotics (sleeping pills). The most important risks of hypnotics include excess mortality (especially overdose deaths, quiet deaths at night, and suicides), infections, cancer, depression, automobile crashes, falls, other accidents, and hypnotic-withdrawal insomnia. Short-term use of one-two prescriptions is associated with even greater risk per dose than long-term use. Hypnotics have usually b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 177 publications
0
32
0
Order By: Relevance
“…Despite concerns about the respiratory safety of sedative-hypnotic agents among persons with OSA (Jordan et al, 2017;Kripke, 2018;Mason et al, 2015), lemborexant did not negatively affect AHI, a measure of OSA severity, and SpO 2 , a key measure of respiratory function, in these participants with mild OSA.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Despite concerns about the respiratory safety of sedative-hypnotic agents among persons with OSA (Jordan et al, 2017;Kripke, 2018;Mason et al, 2015), lemborexant did not negatively affect AHI, a measure of OSA severity, and SpO 2 , a key measure of respiratory function, in these participants with mild OSA.…”
Section: Discussionmentioning
confidence: 70%
“…Sedative-hypnotic drugs, including benzodiazepines and the non-benzodiazepine "Z" drugs, are the most commonly prescribed pharmacologic treatments for insomnia (Sateia, Buysse, Krystal, Neubauer, & Heald, 2017). However, sedative hypnotics are associated with central respiratory depression, which is an important safety consideration for all patients and especially those with OSA (Kripke, 2018). Concerns have been raised that inhibiting arousal during sleep could cause an increase in respiratory events or oxygen desaturation in persons with OSA (Jordan et al, 2017;Mason, Cates, & Smith, 2015).…”
mentioning
confidence: 99%
“…3 Hypnotic sleeping pills, which offer little benefit, 4,5 can be costly and carry risks, including death from overdose, depression, and automobile crashes. [4][5][6] Melatonin supplements, which are processed by the CYP liver enzyme, may interact with drugs processed by the same enzyme (including caffeine and birth control); this may increase plasma melatonin. Melatonin may also interact with hypnotics to cause psychomotor and memory impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Sufficient sleep is critical for health and well-being in older adults (Grandner, 2019), yet 20% to 30% of this population meet the diagnostic criteria for chronic insomnia (Neikrug & Ancoli-Israel, 2010). Increased awareness of sleep's importance to health has coincided with the development, promotion, and increased prescription of sleep medications (Barbee et al, 2018;Bertisch et al, 2014;Grandner, 2019;Mooallem, 2007). Between 1993 and 2007, rates of sleep medication prescriptions increased 30-fold in the United States (U.S.) (Moloney et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, an estimated 3% to 11% of the U.S. population use prescription sleep medications (Aparasu et al, 2003;Bertisch et al, 2014), and long-term use is common (Chong et al, 2013). Although the potential for residual confounding cannot be ruled out, multiple, well-designed studies have found a clear dose-response effect between the use of prescription sleep aids and increased risk of morbidity and mortality (Kripke, 2016;Kripke et al, 2012;Weich et al, 2014). Short-term risks include falls and impaired cognition (American Geriatrics Society Beers Criteria Update Expert Panel, 2015Treves et al, 2018), and long-term risks include neurocognitive disorders (Glass et al, 2005;Kripke et al, 2012).…”
Section: Introductionmentioning
confidence: 99%